Experimental bleaching of a tropical sea anemone in situ. (14th November 2015) - Finn, Maureen H.; Lönnstedt, Oona M.; Rizzari, Justin R.; Jones, Geoffrey P.; Frisch, Ashley J.
Abstract: Bleaching (whitening) of cnidarians such as corals and sea anemones has caused widespread degradation of coral reefs around the world and is therefore an urgent issue for coral reef science and conservation. Although cnidarians often bleach in aquaria, methods for experimental induction of bleaching in wild cnidarians are lacking, which impedes scientists' ability to understand the ultimate effects of bleaching on the broader ecosystem. In this study, we investigated the utility of an in situ method for experimental induction of bleaching in the tropical sea anemone Heteractis crispa . Healthy, wild anemones were covered with opaque black plastic sheets, mesh cages or left undisturbed (controls) and tentacle colour and body size were monitored with a colour reference card and flexible tape, respectively, every 1–3 days for 15 days. Caged and control anemones remained unchanged for the duration of the experiment, but covered anemones commenced whitening after 4–6 days and were completely white after 7–14 days (mean time to bleaching ± SE = 10.1 ± 0.7 days). Experimental bleaching occurred without reduction in anemone body size and was visibly similar to natural bleaching seen previously in H. crispa . We hypothesize that light‐deprivation, reduced water flow, physical contact or some combination of these factors caused the bleaching. This study provides the basis for a simple and rapid method of inducing bleaching in situ, which releases scientists' dependence on sporadic natural bleaching events or artificial aquarium experiments, and provides a means to investigate the effects of bleaching on other ecosystem components such as fishes.